2020
DOI: 10.3390/atmos11030228
|View full text |Cite
|
Sign up to set email alerts
|

Possible Effects of Greenhouse Gases to Ozone Profiles and DNA Active UV-B Irradiance at Ground Level

Abstract: In this paper, we compare model calculations of ozone profiles and their variability for the period 1998 to 2016 with satellite and lidar profiles at five ground-based stations. Under the investigation is the temporal impact of the stratospheric halogen reduction (chemical processes) and increase in greenhouse gases (i.e., global warming) on stratospheric ozone changes. Attention is given to the effect of greenhouse gases on ultraviolet-B radiation at ground level. Our chemistry transport and chemistry climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Simulations with a chemistry climate model (EMAC) for the period 1960–2100 were used to derive trends in DNA-damaging radiation at four mid-latitude locations and one tropical high-altitude site [ 65 ]. DNA-damaging irradiance averaged over the five locations is projected to increase by 1.3% per decade between 2050 and 2100.…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations with a chemistry climate model (EMAC) for the period 1960–2100 were used to derive trends in DNA-damaging radiation at four mid-latitude locations and one tropical high-altitude site [ 65 ]. DNA-damaging irradiance averaged over the five locations is projected to increase by 1.3% per decade between 2050 and 2100.…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionsmentioning
confidence: 99%
“…No trend in total ozone was detected by the model after 2050, and the trend in DNA-damaging irradiance was attributed to a statistically significant (95% CL) decrease in cloud cover of − 1.4 per decade resulting from increasing GHGs. The study suggests that changes in UV-B irradiance at low- and mid-latitudes during the second half of the twenty-first century will be dominated by factors other than changes in stratospheric ozone [ 65 ]. However, these projections depend on the accurate description of clouds by climate models.…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionsmentioning
confidence: 99%
“…Bais et al [11] showed that higher values of UV are expected by the end of the 21st century in tropical areas and a decrease in mid-latitudes, but these estimations still hold high uncertainties. Eleftheratos et al [13] showed that solar UVB irradiance that produces deoxyribonucleic acid (DNA) damage would increase after the year 2050. Such change is driven by a significant decrease in cloud cover due to the evolution of greenhouse gases in the future, suggesting that the process of climate change will overwhelm the effect of ozone recovery on UVB irradiance in the mid-latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the deseasonalized data were used in a multivariate linear regression (MLR) model to describe influences of dynamic origin on total ozone variability. The MLR statistical model includes the QBO, SOLAR, ENSO, NAO, and trend terms, as described by Zerefos et al [24] and later adopted by Eleftheratos et al [25], for further analyses. Those studies, however, had a slightly different approach, as they also included the effects of aerosol optical depth (AOD) and Antarctic oscillation.…”
Section: Data Sources and Methodsmentioning
confidence: 99%